Absorption Parameters for Glucose Solution for Gamma Ray at 59.54 keV - Al-Arif, Maan S.; Kakil, Diyaree O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Photon absorption parameters for glucose solution at different concentrations such as linear attenuation coefficient, mass attenuation coefficient, effective atomic number, electron density and density determined at 59.54 keV photon energy. The mass attenuation coefficient is calculated using the mixture rule and a correction factor to approximate the experimental model is added.  Accordingly, the effective atomic number and electronic density appears to decrease with increasing glucose concentration. Moreover, the measured linear attenuation coefficient and the density for the solution are linearly increased with concentration. We can conclude that the electrical conductivity of the solution depends on the physical nature of the electrical charge carrier in the solution, concentration of the solute material, and the electronic density of the solution at the same time.